taking the sum as 3x^2-10x-8=0
3x^2-12x+2x-8=0
3x(x-4)+2(x-4)=0
(x-4)(3x+2)=0
x=-2/3 or 4
2006-12-10 05:58:59
·
answer #1
·
answered by raj 7
·
0⤊
0⤋
10
2006-12-10 17:03:16
·
answer #2
·
answered by deepak g 1
·
0⤊
0⤋
10
2006-12-10 05:56:40
·
answer #3
·
answered by googlefan 1
·
0⤊
0⤋
Let me presume it is 3x^2-10x-8 = 0
= 3x^2 -12x + 2x - 8 = 0
3x (x - 4) + 2 (x - 4) = 0
(3x + 2) (x - 4) = 0
3x + 2 = 0 x = -2/3
or x - 4 = 0 x = 4
2006-12-10 16:53:28
·
answer #4
·
answered by Srinivas c 2
·
0⤊
0⤋
If you equation is correct (3x*6^2-10x-8=0) then x=4/49
If that isn't how you intended the equation to read, then this is incorrect.
2006-12-10 06:12:35
·
answer #5
·
answered by chriso99 2
·
0⤊
0⤋
X=4/3
X= -2
2006-12-10 06:04:36
·
answer #6
·
answered by dird 2
·
0⤊
0⤋
i think the correct equation is 3x^2-10x-8=0, right?
3x^2-10x-8=0
(3x+2) (x-4) = 0
(3x+2)=0 ; (x-4) = 0 (equate each to 0 )
3x = -2 ; x = 4 (transpose each constant to the right)
x = -2/3 ; x = 4
remember in quadratic equation, there are always two answers... please replace each number to x to check my answers..
2006-12-10 06:04:27
·
answer #7
·
answered by racz_jay25 2
·
0⤊
1⤋
3x²-10x-8=0
(x-4)(3x+2)=0
x=4, -â
2006-12-10 06:25:21
·
answer #8
·
answered by Ranna Renni 2
·
0⤊
0⤋
Do you mean 3x^2 - 10 x - 8?
Ana
2006-12-10 05:56:26
·
answer #9
·
answered by Ilusion 4
·
0⤊
0⤋
3X36-8=10x
108-8=10x
100=10x
x=10
SiMpLe MaTh
2006-12-10 05:58:33
·
answer #10
·
answered by The Slytherin Princess 1
·
0⤊
0⤋